P727 Efficacy of vedolizumab (VDZ) by disease localisation in Crohn's disease. (16th January 2018) - Allez, M; Braegger, F; Kempf, C; Michetti, P
Abstract: Background: In Crohn's disease (CD), disease progression varies according to disease location. It is, therefore, important to assess whether the efficacy of available treatments is maintained across disease locations. Results of the pivotal GEMINI 2 trial suggested that VDZ, a humanised monoclonal α4β7 antibody approved for CD, is efficacious regardless of disease localisation. Methods: A post-hoc analysis was performed on the maintenance phase intent-to-treat (mITT) population of the GEMINI 2 trial to further examine VDZ efficacy by disease localisation and any potential confounding factors. The following efficacy outcomes were assessed at week 52 by disease location (ileum only, colon only, ileocolonic): clinical response (≥70 point reduction in Crohn's Disease Activity Index [CDAI] score from baseline); clinical remission (CDAI score ≤150); and corticosteroid (CS)-free remission in patients receiving CSs at baseline. Logistic regression was performed to assess the impact of disease localisation (ileocolonic vs. colon, ileum vs. colon), prior anti-TNFα therapy, prior CS exposure, concomitant immunomodulator use and baseline calprotectin on clinical remission and clinical response at week 52. Results: The mITT population comprised 461 patients (ileum only: 82; colon only: 117; ileocolonic: 262). In the ileum subgroup, the same proportion of patients receiving VDZ every 8 weeks achieved CS-free remission as those on placebo. In all other patients, VDZ had greater efficacy than placebo at both study dose regimens (every 4 weeks or every 8 weeks) by all three measures of clinical efficacy, irrespective of disease localisation. None of the potential confounding factors included in the logistic regression analysis were found to be significant. Conclusions: VDZ (both dosing regimens) was more efficacious than placebo at improving disease activity in patients with CD. Disease location, prior and/or concomitant therapy, and calprotectin levels did not impact this result. A limitation of this analysis was the small patient numbers in each subgroup; larger studies are required to identify any statistically significant differences.